Efficacy of neem seed oil formulation (Azadirachta indica) against Toxoptera citricida on Siamese orange (Citrus nobilis) plants - Haiqal, Fiqri; Dono, Danar; Hartati, Sri (Fakultas Pertanian, Universitas Padjadjaran, 2026)
Siam citrus (Citrus nobilis Lour.) is one of the important citrus commodities in Indonesia. However, its production can decline due to infestation by the black aphid Toxoptera citricida, which acts both as a sap-sucking pest and as a vector of Citrus Tristeza Virus. Control of this pest by farmers still relies heavily on synthetic insecticides, which may cause environmental pollution, pest resistance, and mortality of non-target organisms. This study aimed to evaluate the effectiveness of a neem seed oil–based botanical insecticide formulation in reducing T. citricida populations on Siam citrus plants and to determine an effective concentration that is relatively safe for non-target organisms. The experiment was conducted using a Randomized Complete Block Design (RCBD) with six treatments, namely a control (water), neem oil formulations at concentrations of 0.75%, 1.0%, 1.25%, and 1.5%, and a synthetic insecticide containing profenofos (0.05%) as a reference treatment. Each treatment was replicated four times. The results showed that the neem seed oil formulation effectively suppressed T. citricida populations, with efficacy increasing as concentration increased. Concentrations of 1.0–1.5% resulted in significantly greater population reductions compared to the control, and the 1.5% concentration achieved efficacy close to 100%, comparable to profenofos at the end of the observation period. In contrast to profenofos, which reduced populations of the predator Cheilomenes lunata and the ant Anoplolepis gracilipes to nearly zero, neem oil application did not exhibit toxic effects on these non-target organisms. Therefore, neem seed oil–based formulations have strong potential as an important component of Integrated Pest Management (IPM) strategies for sustainable Siam orange cultivation.